ANALISIS PENGARUH PENGEMBANGAN KAWASAN MINAPOLITAN TERHADAP PEREKONOMIAN DAN EKOWISATA DI DESA LANGO, KECAMATAN PANTE CEUREUMEN - Taufiq, Taufiq; Amarullah, Amarullah; Ariska, Nana; Hamidi, Hamidi; Insani, Sri Ayu (Universitas Teuku Umar, 2025)
Indonesia as a maritime country has great potential in the fisheries and marine sector. One of the development strategies implemented is the minapolitan concept, namely the development of a fisheries-based area integrated with other supporting sectors. This study aimed at analyzing the impact of minapolitan area development on the economy and ecotourism of community in Lango Village, Pante Ceureumen District. The research method used descriptive quantitative and qualitative through surveys, in-depth interviews, observations, and secondary data analysis. The results showed that the implementation of the minapolitan concept contributed in increasing community income up to 25% in the first year and creating new business opportunities and jobs. In terms of ecotourism, there has been a significant increase in the number of tourists along with the development of supporting infrastructure. However, challenges such as limited infrastructure, community readiness for new technologies, and the risk of natural resource exploitation still need to be considered in the implementation of sustainable policies. Therefore, the minapolitan area management strategy must consider economic, social, and environmental aspects holistically so that the benefits could be savored for a long term.